Exploring High Performance Work Practices as Necessary Condition of HR Outcomes. Issue 2 (December 2019) - Garg, Naval; Punia, B. K.; Jain, Anuradha
The fundamental concept of High Performance Work Practices (HPWPs) constitutes a notion that there exists a work system of HR practices in an organization that may lead to better organizational performance. HPWPs have a positive impact on both individual level performance and organizational level performance. In this light, this paper tends to explore necessity of HPWPs for organizational level outcomes. Outcome variables are job commitment, job satisfaction and work-life balance. Data are analyzed with the help of Necessary Condition Analysis.